Optimizing public accessibility: A review of the urgency of e-government for Bima District - Ramadoan, Syahri; Firman, Firman; Sahrul, Sahrul; Haeril, Haeril (Trigin Publisher, 2024)
This study highlights the urgency of enhancing public accessibility through the implementation of E-Government in Bima District. The research employed a descriptive method with a qualitative approach. The findings indicate that in the context of digital transformation, E-Government becomes a key to improving public access to government services in Bima District, Indonesia. Despite offering significant potential in enhancing efficiency, transparency, and affordability of public services, the implementation of E-Government faces several challenges. Uneven technology infrastructure, low digital literacy, and the lack of trained human resources are among the obstacles that need to be overcome. This study underscores the urgency of enhancing public accessibility through E-Government in Bima District. With a focus on social inclusion, democratic participation, economic aspects, and data security, efforts to address infrastructure constraints, digital literacy, and human resource availability become crucial. Through strategic measures such as technology infrastructure development, enhancement of digital literacy, and inter-agency government coordination, Bima District can achieve significant improvements in public accessibility, increase efficiency in public service, and strengthen community participation in the development process and decision-making